Missionary Imperialists? Missionaries, Government and the Growth of the British Empire in the Tropics, 1860-1885. - Young, F. Lionel (Fides et historia, 2012)
The article reviews the book ''Missionary Imperialists? Missionaries, Government and the Growth of the British Empire in the Tropics, 1860-1885,'' by John H. Darch.